Consumer dissatisfaction: Does the consumer seek redress? - L. F. Pitt; R. Abratt (South African Journal of Business Management, 1984)
Consumer dissatisfaction and redress needs have been the subject of a number of research studies in the USA. The same cannot be said for South Africa. This article reports the findings of research into the South African consumer's dissatisfaction with beauty and health-care products and her actions in seeking redress. Utilizing a successful technique developed by Diener and Greyser, extent of product use, product problems, degree of dissatisfaction, and action in seeking redress are examined. The article concludes that general dissatisfaction with the products concerned is low, but that the problems are of little importance to the consumer. She is also lax in seeking redress, and expects a more positive reaction from the manufacturer than the retailer, although the sample were not inclined to seek redress from the manufacturer. It is apparent that the consumer seeks redress in the easiest alternative - brand switching, and also by means of word-of-mouth. The implications for brand management and product policy are obvious.
Keywords: 650